2006
DOI: 10.1111/j.1365-2133.1975.tb06738.x
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of steroid therapy in hepatic failure

Abstract: SUMMARY Three patients with extensive skin disease and liver failure are described. Two were treated with large amounts of topical corticosteroids and one with a small oral dose of betamethasone. The former two patients developed Addisonian crises when they failed to apply the topical steroids and all three patients developed aseptic necrosis of bone. This report emphasizes that the hazards of steroid therapy may be increased in patients with hepatic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, this problem is usually associated with oral administration or IV injection, and it is quite rare with topical corticosteroid application. Several hips have been reported as showing ONFH following the use of topical corticosteroid ointments [4][5][6][7][8][9][10]; Cunliffe et al [4] first reported two cases of 2 hips in 1975. However, these reports included patients with a medical history of systemic corticosteroid therapy as well as topical corticosteroid treatment or a history of alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%
“…However, this problem is usually associated with oral administration or IV injection, and it is quite rare with topical corticosteroid application. Several hips have been reported as showing ONFH following the use of topical corticosteroid ointments [4][5][6][7][8][9][10]; Cunliffe et al [4] first reported two cases of 2 hips in 1975. However, these reports included patients with a medical history of systemic corticosteroid therapy as well as topical corticosteroid treatment or a history of alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%